Anomalous insertion of extensor hallucis longus and its clinical importance - Shikha S,; Vandana Mehta,; Shweta K,; Suri RK, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Frequent variations are reported in muscles and ligaments of lower limb suggesting that these muscles are yet to achieve the evolutionary fate. Extensor Hallucis longus (EHL) is one such muscle exhibiting anomalies which prove to be of importance while explaining functional anatomy and clinical correlations of the foot. The current study reports unilateral presence of variant EHL tendon encountered during cadaveric dissection of dorsum of foot for undergraduate teaching. The tendon bifurcated into two slips (medial and lateral) at the base of first metatarsal. The main tendinous slip (lateral) was found to be inserted as usual on the dorsal aspect of the terminal phalanx of great toe. The thin medial slip was attached to the medial half of dorsal aspect of base of proximal phalanx of the great toe medial to the insertion of extensor hallucis brevis. An attempt is made to discuss the clinical implications of the variation in the light of available anatomical literature. The results of current study are of clinical relevance to orthopedicians and reconstructive surgeons.